Plateau-like magnetocaloric effect in layered intermetallic compounds activated by tripled magnetic cell. (November 2021) - Wang, X.X.; Wang, W.Q.; Hutchison, W.D.; Su, F.; Xue, Y.F.; Wang, C.W.; Sun, W.; Cadogan, J.M.; Campbell, S.J.; Cheng, Z.X.; Wang, J.L.
Abstract: Energy-efficient and environment-friendly solid-state magnetic refrigeration requires materials with extraordinary magnetocaloric properties. We report the plateau-like magnetocaloric effect activated by tripled magnetic cell in layered intermetallic TbMn2-x Cox Si2 compounds, and the consequent large refrigerant capacity. Substitution of Mn with Co significantly modified the magnetic properties evidenced by two successive ferromagnetic first-order transitions and strong magneto-elasticity as well as significant contraction of the unit cell. Detailed neutron diffraction investigations have established the formation of a tripled magnetic unit cell structure at the temperature range between two magnetic transitions. The overlapping entropy curves near the two transition temperatures results in a plateau-like magnetocaloric effect and enhanced refrigerant capacity. Existence of this special magnetic cell also leads to a variety of interesting physical properties, including a significant drop in resistance and pronounced anomalies in the heat capacity, as well as different responses of the two transition temperatures to an applied magnetic field. The impact of the formation of a tripled magnetic cell on the physical properties is highly unusual for magnetic alloys and merits expanded investigation of this class of magnetic materials to explore for novel applications. Graphical abstract: Image 1 Highlights: TbMn2-x Cox Si2 exhibit large entropy change accompanying two successive transitions resulting in a table-like MCE. Neutron diffraction studies have established the formation of a tripled magnetic cell structure between TC1 and TC2 . Existence of the tripled magnetic cell leads to a significant drop in resistance and anomalies in the heat capacity. Existence of the tripled magnetic cell leads different responses of two transition temperatures to an applied magnetic field.